Universal Design for Learning: The More, the Better? - Marvin Roski; Malte Walkowiak; Andreas Nehring (MDPI AG, 2021)
An experimental study investigated the effects of applying principles of the Universal Design for Learning (UDL). Focusing on epistemic beliefs (EBs) in inclusive science classes, we compared four groups who worked with learning environments based more or less on UDL principles and filled out an original version of a widely used EBs questionnaire or an adapted version using the Universal Design for Assessment (UDA). Based on measurement invariance analyses, a multiple indicator, and multiple cause (MIMIC) approach as well as multi-group panel models, the results do not support an outperformance of the extensive UDL environment. Moreover, the UDA-based questionnaire appears to be more adequately suited for detecting learning gains in an inclusive setting. The results emphasize how important it is to carefully adopt and introduce the UDL principles for learning and to care about test accessibility when conducting quantitative research in inclusive settings.